2019
DOI: 10.1021/acsami.9b06569
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Time-Dependent Oxygen Surface Exchange Kinetics with Surface Chemistry of La0.6Sr0.4Co0.2Fe0.8O3−δ Catalysts

Abstract: The Sr segregation at the surface of a perovskite La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF) oxygen electrode is detrimental to the electrochemical performance and durability of energy conversion devices such as solid oxide fuel cells. However, a quantitative correlation of degradation of the oxygen surface exchange kinetics with Sr precipitation formation at the LSCF surface is not clearly understood yet. Herein, the correlation of the time-dependent degradation mechanisms of the LSCF catalysts with respect to Sr segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…Strontium segregation has predominantly been reported as a steady increase from bulk stoichiometry to near 100% coverage at the surface, 16,29 although some reports observe subsurface strontium depletion. 25,32 This work conrms the presence of this sub-surface strontium depletion region, however, it also opens the question as to which pathway the strontium (and the lanthanum) is able to diffuse through the material. Kubicek et al showed that, in Pulse Laser Deposited (PLD) La 0.6 Sr 0.4 -CoO 3Àd thin lms, at 720 C the strontium self-diffusion coef-cient (D g ) is on the order of 10 À18 cm 2 s À1 and strontium selfdiffusion coefficient in a grain boundary (D gb ) was on the order of 10 À15 cm 2 s À1 .…”
Section: Strontium Diffusion and Segregationmentioning
confidence: 88%
See 1 more Smart Citation
“…Strontium segregation has predominantly been reported as a steady increase from bulk stoichiometry to near 100% coverage at the surface, 16,29 although some reports observe subsurface strontium depletion. 25,32 This work conrms the presence of this sub-surface strontium depletion region, however, it also opens the question as to which pathway the strontium (and the lanthanum) is able to diffuse through the material. Kubicek et al showed that, in Pulse Laser Deposited (PLD) La 0.6 Sr 0.4 -CoO 3Àd thin lms, at 720 C the strontium self-diffusion coef-cient (D g ) is on the order of 10 À18 cm 2 s À1 and strontium selfdiffusion coefficient in a grain boundary (D gb ) was on the order of 10 À15 cm 2 s À1 .…”
Section: Strontium Diffusion and Segregationmentioning
confidence: 88%
“…Many reports show enhance strontium concentrations over approximately the rst 6-20 nm of the material, 16,[28][29][30][31] however, strontium deciency has also been observed over the same depth scale. 25,32 Additionally, no correlation has been made between the changes in immediate sub-surface composition and oxygen exchange/transport properties in MIECs.…”
Section: The Sub-surfacementioning
confidence: 99%
“…As the SrO is an electrical insulating compound blocking the reactions of oxygen exchange, the process leads to the LSCF surface passivation [21,22,23,24]. For example, Wang et al [23] have shown that the global exchange kinetic constant after ageing at 700°C-800°C is decreased by an order of magnitude and they attributed this evolution to the LSCF surface passivation.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kim et al [22] have recently suggested that the decrease of 'cannot be accounted for only the surface coverage of inactive Sr segregation' and they proposed that the kinetic constant could also be affected by the stoichiometry change with Sr deficiency on the 'clean' part of the LSCF surface. Moreover, the oxygen chemical diffusivity (or ionic conductivity) of LSCF is also decreased by the loss of Sr in the bulk of electrode due to the LSCF decomposition [22,25]. All these phenomena are expected to cause the degradation of the electrode performances even if their impact on the electrode response remains nowadays unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation